Bioinspired four-dimensional polymeric aerogel with programmable temporal-spatial multiscale structure and functionality. (12th April 2021) - Wang, Wenxin; Du, Liwen; Xie, Yu; Zhang, Fenghua; Li, Peng; Xie, Fang; Wan, Xue; Pei, Qibing; Leng, Jinsong; Wang, Ning
Abstract: The original four-dimensional (4D) polymeric aerogel design introduces a concept of programmable temporal-spatial multiscale structure, in which the fourth dimension is time. The novel aerogel possesses shape memory properties, which can fix temporary state and recover permanent state by releasing frozen stress under stimulus without any sophisticated electro-mechanical equipment in the programmable manner. Its structure can be tailored by precrosslinked ice template method to obtain high permeable multiscale structure. Its functionalities and performances can be customized and optimized by adjusting porous framework, matrix, functional groups, and self-adaptivity based on application demands. Comparing with traditional aerogels, the emerging 4D aerogel has many unique properties, including excellent self-adaptivity, high permeable multiscale structure, flexible preprogrammed ability, customized functional groups, low cost, and environmental friendliness. Its exploration and development could draw much attention due to various promising potential applications including water treatment, intelligent structure, and sensor. These high-value applications would further promote the development of the intelligent aerogels and the reliable preparation technologies. As an interesting field, the 4D aerogel idea is revolutionary for traditional aerogels and expected to provide new perspective and practical approach to realize the integration of material, structure, and functionality. Graphical abstract: Image 1 Highlights: Propose original 4D aerogel with temporal-spatial multiscale structure. The ability to change state with time in the programmable manner. Flexibly and systematically adjusted by programmable and precrosslinked strategy. High permeable 3D multi-scale structure. Generally unavailable in other types of traditional or deformable aerogels.